Usage of FEM for synthesis of dead-beat current controller for permanent magnet synchronous motor. Issue 5 (2nd September 2019) - Palka, Ryszard; Piotuch, Rafal
Abstract : Purpose: Predictive controllers and permanent magnet synchronous motors (PMSMs) got more attention over the past decades thanks to their applicable features. This paper aims to propose and verify a method to design a predictive current controller with consideration of motor characteristics obtained from finite element analysis (FEA). Design/methodology/approach: Permanent magnet motor parameters and its maps can be calculated by means of FEA. The model takes into account magnetic saturation and thermal electro-magnetic properties. For each dq current vector and each position, self and mutual inductances are calculated. Based on co-energy method and fundamentals of coordinate transformation dynamic and static, dq inductances are obtained. These are used in classical and modified dead-beat current controller equations. Findings: To sustain good features of a controller over higher current regions, it is necessary to adapt control law of a dead-beat controller. After its modification, control quality can be superior over classical solution in high saturation regions. The transient simulations of controller and motor give accurate results. Originality/value: Common predictive current controllers use nominal motor parameters in their equations. The authors proposed a modified dead-beat current controller to improve the control quality. There is no need to apply self-tuning algorithms, and implementation of the controller is not much more complicated than that of the classical controller. Designer of a control system can obtain required data from motor designer; in design process of modern machines such data are often already available. The proposed methodology increases control quality of the presented dead-beat controller.